Drinking water services in the primary schools: evidence from coastal areas in Bangladesh. Issue 6 (June 2022) - Hossain, Mohammad Jobayer; Islam, Md. Ansarul; Rahaman, Md. Hasibur; Chowdhury, Md. Arif; Islam, Md. Atikul; Rahman, Mohammad Mahfuzur
Abstract: Salinity intrusion both in surface and groundwater caused a crisis for safe drinking water in coastal Bangladesh. The situation is even worse for children especially at school. However, information on water services in coastal schools is limited. Here we assess the quality of drinking water and supply infrastructures in the primary schools of a severely saline affected coastal area of Bangladesh. To fulfill the objective, thirty-eight schools were purposively selected and investigated in Dacope Upazila of Khulna district in Bangladesh. Findings revealed that harvested rainwater (63%) and pond (21%) are the major drinking water sources where countries' leading water supply technology, tube well (16%) were the least used option. Moreover, salinity in all the tube wells exceeded the national standard. DO, pH, NO3, SO4 and PO4 concentration of all options satisfied national standards. However, total coliform counts exceeded the national standard. More than half of the samples had a low to high risk of indicator bacteria which is a major public health concern. Although 29% schools have installed portable water filtration units, those are grossly inaccessible for the students. Hence, students are reportedly consuming unsafe drinking water, and thus are vulnerable to water-borne diseases. The lack of resources and poorly designed infrastructure are the principal challenges to the safe drinking water supply. Therefore, disinfection at the point of use along with proper maintenance of the water infrastructure is urgent needs to safeguard potable water services in the primary schools of coastal Bangladesh. Graphical abstract: Image 1 Highlights: 38 primary schools were evaluated for drinking water quality covering all sources. Microbial contamination at both sources and point of use was identified. 1 in 5 school depends heavily on the contaminated surface water sources. 3 in 10 schools had water filtration facilities, primarily for the teachers. About half of the sources can be identified as highly risky based on E. coli count. Abstract : Coastal Bangladesh; Drinking water; Primary school; Water quality; Water supply.